2013
DOI: 10.1002/alr.21200
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal quality of life outcomes after minimally invasive resection of sinonasal and skull‐base tumors

Abstract: MIER results in overall improvement in SNOT-20 scores, with greater change being noted in females and in patients with benign tumors. Prior smoking and chemoradiation strongly predict decreased improvement in sinonasal QOL after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 27 publications
2
42
1
Order By: Relevance
“…Additional research has focused on QOL outcomes in patients undergoing endoscopic resection of sinonasal tumors without NSF. Harrow et al reported that mean SNOT‐20 scores as well as scores for questions corresponding to the rhinologic and ear/facial subdomains were improved at 3 and 6 months after surgery relative to preoperative levels but that the improvement was only found in patients with benign tumors . In looking at long‐term outcomes, the significant improvements for patients with benign tumors seen 6 months after surgery were not sustained at 1 or 2 years after surgery, although patients with malignant tumors did have improved psychological and sleep subdomain scores at these later time points .…”
Section: Discussionmentioning
confidence: 99%
“…Additional research has focused on QOL outcomes in patients undergoing endoscopic resection of sinonasal tumors without NSF. Harrow et al reported that mean SNOT‐20 scores as well as scores for questions corresponding to the rhinologic and ear/facial subdomains were improved at 3 and 6 months after surgery relative to preoperative levels but that the improvement was only found in patients with benign tumors . In looking at long‐term outcomes, the significant improvements for patients with benign tumors seen 6 months after surgery were not sustained at 1 or 2 years after surgery, although patients with malignant tumors did have improved psychological and sleep subdomain scores at these later time points .…”
Section: Discussionmentioning
confidence: 99%
“…Quality of life transiently worsens in the early period following surgery, but significantly improves in the months later [25,26]. Out of the 7 series we identified as reporting the spectrum of sinonasal morbidities after EESBS, only 3 reported the time for sinonasal signs and symptoms resolution as shown in Table 2.…”
Section: Time To Resolve Nasal Signs and Symptomsmentioning
confidence: 99%
“…Several questionnaires and tools have been introduced and used in clinical studies of endoscopic skull base surgery to assess QoL morbidity and sinonasal outcomes. These include Short Form-36 (SF-36), Anterior Skull Base Questionnaire (ASBQ), Rhinosinusitis Outcome Measure (RSOM)-31, Sinonasal Outcome Test (SNOT)-20, SNOT-22, and many others [6,7,24,26,[28][29][30][31][32][33]. However, due to several different questionnaires and no standardized definition for QoL, it is hard to compare different studies.…”
Section: Quality Of Life (Qol)mentioning
confidence: 99%
“…Improvement in sinonasal quality of life (QoL) following endoscopic sinus surgery for inflammatory disease such as chronic rhinosinusitis has been well-documented across the literature. Whereas many studies have evaluated sinonasal QoL within the first year of surgery for patients undergoing malignant tumor resection, [3][4][5][6][7][8][9] only one series has evaluated long-term QoL in this patient population. 10 Although this cohort study demonstrated improvement in QoL with respect to psychological and sleep parameters, it showed no improvement in rhinologic QoL following malignant tumor resection at 2-year follow-up.…”
Section: Introductionmentioning
confidence: 99%